1998
DOI: 10.1016/s1074-7613(00)80663-9
|View full text |Cite
|
Sign up to set email alerts
|

Schlafen, a New Family of Growth Regulatory Genes that Affect Thymocyte Development

Abstract: The Schlafen (Slfn) family of genes are differentially regulated during thymocyte maturation and are preferentially expressed in the lymphoid tissues. Ectopic expression of the prototype member Slfn1 early in the T lineage profoundly alters cell growth and development. In these mice, the DP thymocytes fail to complete maturation, and, depending on the transgene dosage, the number of thymocytes is reduced to 1%-30% of normal. Furthermore, expression of the Schlafen family members in fibroblasts and thymoma cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
260
1
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(279 citation statements)
references
References 45 publications
11
260
1
1
Order By: Relevance
“…Several genes involved in cellular differentiation rather than activation, such as ornithine decarboxylase, B cell translocation gene 1 (BTG 1), JunB, and Schlafen 2, show ''high-moderate'' expression in SP thymocytes. Expression of BTG 1 and BTG 2 and Schlafen 2 is up-regulated in quiescent lymphocytes and may maintain cells in G 0 ͞G 1 (26,27). JunB, which can also maintain highly differentiated cells in the resting state (16), is expressed at higher levels in CD4 vs. CD8 SP thymocytes (21 vs. 4) (Fig.…”
Section: Resultsmentioning
confidence: 96%
“…Several genes involved in cellular differentiation rather than activation, such as ornithine decarboxylase, B cell translocation gene 1 (BTG 1), JunB, and Schlafen 2, show ''high-moderate'' expression in SP thymocytes. Expression of BTG 1 and BTG 2 and Schlafen 2 is up-regulated in quiescent lymphocytes and may maintain cells in G 0 ͞G 1 (26,27). JunB, which can also maintain highly differentiated cells in the resting state (16), is expressed at higher levels in CD4 vs. CD8 SP thymocytes (21 vs. 4) (Fig.…”
Section: Resultsmentioning
confidence: 96%
“…One large category representing 44 of the 177 differentially expressed genes are genes induced during positive selection but not by TCR signaling. This category includes many genes previously described to be induced during positive selection, such as CD53, IL-6R␣, and schlafen 1 (18)(19)(20), and some genes whose expression pattern during positive selection has not been previously characterized, such as semaphorin 4A, PKC-, and the serine protease inhibitor, serpin1b. This cluster may include genes that require thymic stromal cell factors in addition to TCR signaling for their induction.…”
Section: Resultsmentioning
confidence: 99%
“…42,43 SLFN11, a member of the SLFN family, potently and specifically abrogates the production of retroviruses, e.g., human immunodeficiency virus (HIV-1). 33 Using cells with endogenously high and low SLFN11 expression and siRNA-mediated silencing, Zoppoli et al 44 found that SLFN11 causally determines cell death and cell cycle arrest in response to DNA-damaging agents in cancer cells from different tissues of origin.…”
Section: Discussionmentioning
confidence: 99%